The Correlation Between ABPM Parameters and Left Ventricular Hypertrophy in Pediatric Essential Hypertension - Wu, Haojie; Shi, Lin; Lin, Yao; Zheng, Tong (Frontiers in Pediatrics, 2022)
Objective To explore the association of dipping pattern and blood pressure load with left ventricular hypertrophy (LVH) in pediatric essential hypertension. Materials and Methods Through an echocardiography monitor and an ambulatory blood pressure monitor of 425 children and adolescents diagnosed with essential hypertension with no treatment received, we identified 140 cases of LVH. Grouping patients according to LVH (LVH, N = 140; n-LVH, N = 285), we further evaluated their ambulatory blood pressure monitoring (ABPM) parameters by comparing dipping patterns between groups. A multivariable logistic regression analysis was used to determine the effect of blood pressure load on LVH. Results No significant difference was found in systolic or diastolic blood pressure dipping patterns between groups (P = 0.161, P = 0.139). However, compared to the n-LVH group, the LVH group presented significant elevated nighttime systolic blood pressure (SBP) (P < 0.05), while nighttime DBP remained stable (P = 0.391), resulting in higher daytime and nighttime SBP loads, higher nighttime DBP load, and higher 24-h SBP load (P < 0.05). Notably, our multivariable logistic regression has shown that this trend of 24-h SBP load acts independently as a critical risk factor for LVH. Conclusion Collectively, we observed a correlation between BP load and LVH in pediatric hypertension. Our data demonstrated that SBP load has a more significant weight in LVH progression, and 24-h SBP load, in particular, acts as a critical early prognostic parameter for LVH in pediatric hypertension.